COVID-19 and Oral Fluids - Gaudin, Alexis; Badran, Zahi; Chevalier, Valérie; Aubeux, Davy; Prud'homme, Tony; Amador del Valle, Gilles; Cloitre, Alexandra (Frontiers in Dental Medicine, 2020)
The coronavirus disease 2019 (COVID-19) is an acute infectious disease that has led to a global pandemic. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for this infection. This virus enters the body through the mucous membranes (oral, nasal, or conjunctival ocular) or the skin and replicates in the respiratory system (nasal cavity, throat, and the lung) but may cause damage to other systems and organs. Main transmission is through saliva droplets and oral fluids (OF) including saliva and non-salivary elements that contain infective viral loads of the virus. SARS-Cov-2 enters cells via receptor angiotensin-converting enzyme II (ACE2) and the action of an enzyme (furin) that cleaves the viral envelope and enhances the infection of the host cells. Although the origin, mechanism, and dynamics of SARS-CoV-2 in OF remain to be elucidated, its presence in OF is now established. Therefore, OF might be a diagnostic or monitoring tool for COVID-19 either alone or in combination with other tests in addition to the clinical examination. Moreover, the presence of SARS-CoV-2 in OF raises the question of the management of the infectious risk for dental practice. There is an urgent need to inform the dental community and ensure measures to protect dentists and dental staff from the new SARS-CoV-2. This comprehensive review of COVID-19 and oral health depicts the roles of OF in the transmission dynamics of SARS-CoV-2 and discusses the value of OF as a diagnostic tool and focuses on the management of risk transmission related to OF in dental practice.